2012
DOI: 10.1002/jmri.23585
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of MR elastography and anatomic MR imaging features in the diagnosis of severe hepatic fibrosis and cirrhosis

Abstract: Purpose To compare the diagnostic accuracy of MR elastography and anatomic MR imaging features in the diagnosis of severe hepatic fibrosis and cirrhosis. Materials and Methods Three readers independently assessed presence of morphological changes associated with hepatic fibrosis in 72 patients with liver biopsy including: caudate to right lobe ratios, nodularity, portal venous hypertension (PVH) stigmata, posterior hepatic notch, expanded gallbladder fossa and right hepatic vein caliber. Three readers measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 34 publications
(59 reference statements)
7
84
0
3
Order By: Relevance
“…As reported by Rustogi et al [105] stiffness measurements are repeatable with high overall inter-reader agreement (P=0.74); thus, MRE shows potential for longitudinal monitoring of patients. Furthermore, Yin et al found that this technique has a high negative predictive value (97%) for excluding the presence of fibrosis, suggesting that MRE could have a role for improving the ability to risk-stratify patients for liver biopsy [102].…”
Section: Mr Elastographysupporting
confidence: 65%
“…As reported by Rustogi et al [105] stiffness measurements are repeatable with high overall inter-reader agreement (P=0.74); thus, MRE shows potential for longitudinal monitoring of patients. Furthermore, Yin et al found that this technique has a high negative predictive value (97%) for excluding the presence of fibrosis, suggesting that MRE could have a role for improving the ability to risk-stratify patients for liver biopsy [102].…”
Section: Mr Elastographysupporting
confidence: 65%
“…lobe-to-right lobe width ratio has only moderate overall interreader agreement, with a k value of 0.53 (22). Signs of portal hypertension are indirect markers for cirrhosis.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Investigators have demonstrated that MR elastographic values are better than morphologic features on MR images for the prediction of advanced fibrosis and cirrhosis (22,26).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Wang et al [73] 2012 Meta-analysis 1. Rustogi et al [54] 2012 Retrospective 1. to-noise limitations; (2) a longer examination time than SSI; (3) the need for dedicated installation equipment; and (4) a lack of comparable studies between 1.5 Tesla and 3.0 Tesla MRI machines and among other company products (Table 2). Therefore, an absolute cut-off value for diagnosis and grading of hepatic fibrosis has not been established.…”
Section: Cut-offs Auroc Fibrosis Scorementioning
confidence: 99%
“…This study also showed that MRE could discriminate patients with moderate and severe fibrosis (grades 24) from those with mild fibrosis (sensitivity, 86%; specificity, 85%). Several studies show that MRE is more reliable for staging hepatic fibrosis compared to DWI and conventional MRI, with a powerful combination of sensitivity, specificity, likelihood ratios, diagnostic odds ratio, and area under the summary receiver operating characteristic curve values [51,[53][54][55] (Table 2). MRE can be easily added to standard abdominal MRI protocols, promising value added in staging liver cirrhosis.…”
Section: Mrimentioning
confidence: 99%